How to avoid errors in the translation of papers into English? A case study - Moreno Loaiza, Milagros (2016)
Mr. Editor: We read with interest the article "Barriers to safe abortion under Peruvian law" published in the latest issue of its magazine (1). The article is in English version in Scielo-Peru, and in Spanish and English on the website of the magazine. In this regard we analyze the version published in English and found a translation error in two paragraphs that change the meaning of the statement in the article, and suggest the commission of crimes in public hospitals in Peru. Paragraphs presented in Table 1.